Investigating the Effect of Structural Transformation on the Efficiency of VAT Collection in the Provinces in Iran - Ali Akbar Arabmazar; Hojjat Izadkhasti; Sarah Yavari (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2021)
Value-added tax is levied at various stages of the import, production, distribution, and consumption chain based on a percentage of the value of goods sold or services provided at each stage and ultimately paid by the final consumer. Structural transformation is considered as one of the variables affecting the efficiency of VAT collection often has led to an increase in the share of services in the total value added of the economy. In this study, the effect of structural transformation on the efficiency of VAT collection in provinces of Iran during 2008-2016. The results indicate that the ratio of value added of the service sector to total value added has a negative and significant effect on the efficiency of VAT collection. The value-added ratio of the services sector to the value added of the industrial sector has a negative and significant effect on the efficiency of VAT collection. Also, GDP growth per capita, Gini coefficient and the interval of value-added ratio of the agricultural sector of total value added has a negative effect on the efficiency of VAT collection. The rate of urbanization and the ratio of construction expenditures to total government expenditures have a positive and significant effect on the efficiency of VAT collection in the provinces.